Research on the Design of Intelligent Energy Efficiency Management System for Ships Based on Computer Big Data Platform. Issue 2 (February 2021) - Li, Fangxuan; Gao, Wenxue
Abstract: In the process of protecting ecological environment, constructing ecological civilization and constructing harmonious environment between man and nature, energy efficiency management is our only way. In this paper, the design of ship intelligent energy efficiency management system using computer big data is introduced from three main components, and the functions of the main system are given.